PENGGUNAAN INTERACTIVE POWERPOINT APLIKASI BERPORI DI KELAS PENERJEMAHAN - Kartika Dewi Nugroho (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
Integrating technology into classroom activities is necessary, especially in this digital era. Technology helps the classroom to be more engaging because nowadays we are offered many choices of technology-based teaching-learning media. Teacher can improve their creativity by utilizing the technology that are presented in the form of learning apps or social media. Developing the learning teaching media using technology can motivate students to learn actively. Moreover, in time of pandemic when teaching and learning activities are done remotely, activity with technology-based is very helpful to maintain students’ engagement toward the lesson. Besides, the material will be delivered more easily with the help of technology in classroom. This research aims to find students’ perception towards the use of Interactive PowerPoint Aplikasi Berbasis Powerpoint Interaktif (Aplikasi Berpori) in translation classroom. This app is one example of technologies that is used in the classroom to deliver the learning material. The participants of this research are 58 students from Universitas Mahasaraswati Denpasar Bali who have practiced their translation using Interactive PowerPoint. The data is analysed using descriptive qualitative based on the questionnaire and open-ended questions. The result of this research shows that the students are interested and give positive perception toward the use of Aplikasi Berpori for translation practice.